2007
DOI: 10.1016/j.jbiomech.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage mechanical and biochemical property relations before and after in vitro growth

Abstract: The aim of this study was to design in vitro growth protocols that can comprehensively quantify articular cartilage structure-function relations via measurement of mechanical and biochemical properties. Newborn bovine patellofemoral groove articular cartilage explants were tested sequentially in confined compression (CC), unconfined compression (UCC), and torsional shear before (D0 i.e. day zero) and after (D14 i.e. day 14) unstimulated in vitro growth. The contents of collagen (COL), collagen-specific pyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 32 publications
10
62
1
Order By: Relevance
“…This further supports the minipig model for translational biomedical research. Contrary to the oft-reported structure-function relationship of articular cartilage that correlates GAG content with compressive properties, 36 for humans, minipigs, and FPs, the TMJ disc's compressive properties trended lower in the central regions despite higher GAG content in these regions. 12,13 Thus, components beside GAGs likely contribute to disc compressive properties; for example, the mean diameter of collagen fibril correlated with the compressive properties of the human intervertebral disc's annulus fibrosus.…”
Section: Discussioncontrasting
confidence: 85%
“…This further supports the minipig model for translational biomedical research. Contrary to the oft-reported structure-function relationship of articular cartilage that correlates GAG content with compressive properties, 36 for humans, minipigs, and FPs, the TMJ disc's compressive properties trended lower in the central regions despite higher GAG content in these regions. 12,13 Thus, components beside GAGs likely contribute to disc compressive properties; for example, the mean diameter of collagen fibril correlated with the compressive properties of the human intervertebral disc's annulus fibrosus.…”
Section: Discussioncontrasting
confidence: 85%
“…For instance, AC has been shown to have highly non-linear equilibrium tension and compression properties where the tissue has a much higher Young's modulus in tension than in compression (Soltz and Ateshian 2000;Williamson et al 2003;Huang C-Y et al 2005;Ficklin et al 2007). …”
Section: Table Of Contentsmentioning
confidence: 99%
“…While these models strive to develop PG models that are based on physically realistic continuum electromechanical interactions, they often require the determination of difficult to measure quantities such as fixed charge density, or glycosaminoglycan (GAG) molecule radius, and can result in overestimation of PG swelling stress and numerical instability in finite element analysis (FEA) (Klisch 2007;Davol et al 2008;Buschmann and Grodzinsky 1995 Studies have shown that the immature and mature AC equilibrium aggregate modulus ( ) and AC compressive modulus ( ), may initially decrease then increase with increasing compressive strains (Ficklin et al 2001;Wang et al 2003;Williams et al 2010). Therefore, it is hypothesized that under large compressive strains (>15% -45%) the COL fibers should undergo a transition from tension to compression.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…Computer-guided study designs can be helpful in this context, and using computers to interpret and extrapolate experimental data may turn out to be the only way to break through the trial-and-error-like approaches that are adopted nowadays. In the past few years many different theoretical models for cartilage mechanics have been developed [82][83][84][85][86][87][88][89]. These models form the basis for computer models that are dedicated for describing cartilage tissue engineering [33,72,[90][91][92][93][94][95][96][97].…”
Section: Current and Future Developmentsmentioning
confidence: 99%